2020
DOI: 10.1039/d0tc00029a
|View full text |Cite
|
Sign up to set email alerts
|

Flexible TPU strain sensors with tunable sensitivity and stretchability by coupling AgNWs with rGO

Abstract: The layer-by-layer structure formed by the synergistic effect of GO and AgNWs endows the strain sensors with high sensitivity and a wide working range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 69 publications
0
74
1
Order By: Relevance
“…In this work, an electrospinning TPU fibrous film was chosen as the polymer matrix to produce a strain sensor. For conductive carbon nano-fillers of CPCs, they are widely used that zero-dimension carbon black (CB) [24,25], onedimensional carbon nanotubes (CNTs) [26][27][28][29] and carbon fibers (CFs) [30], and two-dimensional graphene and MXene [31][32][33][34]. Because of the massive industrial production, processing convenience and economic availability, conductive CB particles were used.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, an electrospinning TPU fibrous film was chosen as the polymer matrix to produce a strain sensor. For conductive carbon nano-fillers of CPCs, they are widely used that zero-dimension carbon black (CB) [24,25], onedimensional carbon nanotubes (CNTs) [26][27][28][29] and carbon fibers (CFs) [30], and two-dimensional graphene and MXene [31][32][33][34]. Because of the massive industrial production, processing convenience and economic availability, conductive CB particles were used.…”
Section: Introductionmentioning
confidence: 99%
“…[ 81 ] Although low‐GF sensors are viable for measuring large dynamic motions (e.g., knee bending), the accurate monitoring of subtle muscle motions (e.g., blinking) requires sensors with a high GF. [ 82–84 ] Moreover, high sensitivity ensures a high signal‐to‐noise ratio, which helps achieve high measurement accuracy. In an AR/VR system, a fast response is another important factor for real‐time human motion detection, and it can help minimize device latency.…”
Section: Nanowire‐based Wearable Skin Sensory Input Interfacesmentioning
confidence: 99%
“…Recently, nanowire‐based strain gauges have drawn considerable research attention owing to their excellent conductivity, stretchability, and flexibility. [ 56,83,87,88,99,102–105 ] As shown in Table 1 , many studies have reported nanowire‐based strain gauges for monitoring human motions between 2015 and 2020. These applications can be categorized into nine types based on the type of motion it monitors: facial, throat, neck, body posture, elbow/knee, wrist, opisthenar, finger, and foot.…”
Section: Nanowire‐based Wearable Skin Sensory Input Interfacesmentioning
confidence: 99%
“…In this regard, graphene, carbon nanotubes, and other carbon nanoparticles, such as carbon black, have been widely explored, among others. The addition of these nanoparticles to polymers with high strain capabilities such as fluoroelastomers [37], thermoplastic polyurethane [38], or vulcanized silicone [39] has demonstrated excellent sensing capabilities. More specifically, they present enormous potential for human motion sensing or wearable electronics [37] as the GF at high strain levels (>20%) can be in the range of 400-4000 depending on the content and morphology of the carbon nanofiller.…”
Section: Shm In Nanocomposite Coatingsmentioning
confidence: 99%